Characterization of two midgut proteinases of helicoverpa armigera and their interaction with proteinase inhibitors - Telang, M. A.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
Two serine proteinases from the midgut of Helicoverpa armigera have been partially purified and characterized. One proteinase, HGP-1, was capable of hydrolyzing a synthetic substrate of elastase and was inhibited by elastatinal. The second proteinase, HGP-2, was inhibited by a trypsin inhibitor. Molecular weights of HGP-1 and HGP-2 were approximately 26.0 and 29.0 kDa, respectively. Both the proteinases exhibited alkaline pH optima in the range of 10-11. Furthermore, interaction of HGP-1 and HGP-2 with proteinase inhibitors (PIs) from host and non-host plants was studied. HGP-1 was not only insensitive to a PI from chickpea (host) but was also able to degrade it. The same PI from chickpea was able to inhibit over 50% activity of HGP-2. On the contrary, PIs from potato (non-host) showed strong inhibition of both, HGP-1 and HGP-2 and also demonstrated protection of chickpea seed proteins from digestion by both the HGPs. These results could provide important clues in designing strategies for sustainable use of plant PIs in developing insect-tolerant transgenic plants. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: elastase; Helicoverpa armigera gut proteinases; insect-resistant plants; plant proteinase inhibitors